Implementation of modified Q learning technique in EMCAP control architecture - Ganesha, D.; Venkatamuni, Vijayakumar Maragal (International Journal of Engineering and Technology, 2017)
This research introduces a self learning modified (Q-Learning) techniques in a EMCAP (Enhanced Mind Cognitive Architecture of pupils). Q-learningÂ is a modellessÂ reinforcement learning (RL) methodologyÂ technique. In Specific,Â Q-learning can be applied to establish an optimal action-selection strategy for any respectiveÂ Markov decision process. In this research introduces the modified Q-learning in a EMCAP (Enhanced Mind Cognitive Architecture of pupils). EMCAP architecture [1] enables and presents various agent control strategies for static and dynamic environment.Â Experiment are conducted to evaluate the performace for each agent individually. For result comparison among different agent, the same statistics were collected. This work considered varied kind of agents in different level of architecture for experiment analysis. The Fungus world testbed has been considered for experiment which is has been implemented using SwI-Prolog 5.4.6. The fixed obstructs tend to be more versatile, to make a location that is specific to Fungus world testbed environment. The various parameters are introduced in an environment to test a agentâ€™s performance.his modified q learning algorithm can be more suitable in EMCAP architecture.Â The experiments are conducted the modified Q-Learning system gets more rewards compare to existing Q-learning.